PENGARUH PENGUASAAN STRUKTUR PASAR TERHADAP HASIL BELAJAR EKONOMI PADA MATERI POKOK PERDAGANGAN INTERNASIONAL SISWA KELAS XI IPS SMA NEGERI 1 PANYABUNGAN - Mara Judan Rambey; Umar Kholil Lubis (Pendidikan Sejarah, 2023)
This study aimed to determine the extent of a significant relationship between the market structure subjek mastery With Learning Outcomes Understanding Economics In Topic International trade class XI IPS SMA Negeri 1 Panyabungan. The population of this study were all students of class XI IPS SMA Negeri 1 Panyabungan which consists of 3 parallel classes totaling 105 people. Sampling technique with total sampling techniques by drawing. So that all of the population to be sampel. To capture market share data on capital and learn to understand the market structure in the form of a test instrument. Descriptive analysis of the calculation results, the average value of the the market structure subjek mastery (variable X) by 70.97 to get in on the category of